FUNCTIONAL LIMITATIONS ARISING FROM CHANGES IN RESPIRATORY MECHANICS IN CHRONIC OBSTRUCTIVE PULMONARY DYSFUNCTION - Gomes Ferreira, Veronica; Lajana Oliveira de Almeida, Mônica (Health and Society, 2021)
INTRODUCTION obstructive pulmonary disease is a common preventable and treatable disease where an obstruction leads to various respiratory changes such as impaired airflow, leading to several changes occurring in the mechanics of the respiratory muscles, alters the conformation of the chest and diaphragm, mainly causing dyspnea and limitations as limitations. This research aims to correlate limitations according to changes in respiratory mechanics. (MATERIALS AND METHODS) the present is an integrative literature review, for the search for articles were used as databases PUBMED and SCIELO, studies were included without distinction of language and year, published and indexed in the databases free of charge and in full, studies that associated COPD with other respiratory diseases were excluded, studies where the reserves had undergone lung surgery, and studies that did not bring complete results. (RESULTS) 52 studies were found in total, 15 duplicates were excluded, in the first selection stage 19 studies were excluded, in the second stage 10 studies were excluded, thus the review sample of 9 studies, of the clinical trial type. (CONCLUDING REMARKS)Among the most prevalent limitations we saw low tolerance and resistance to physical exercises, limitations to perform activities of daily living, leading to dyspnea and dysfunction of the respiratory muscles, affecting the happy quality of life.